Motivational Interviewing among HIV Health Care Providers: Challenges and Opportunities to Enhance Engagement and Retention in Care in Buenos Aires, Argentina. (November 2015) - Bofill, Lina; Weiss, Stephen M.; Lucas, Mar; Bordato, Alejandra; Dorigo, Analia; Fernandez-Cabanillas, Graciela; Aristegui, Ines; Lopez, Maria; Waldrop-Valverde, Drenna; Jones, Deborah
In Argentina, providers' response to motivational interviewing (MI) to improve engagement and retention in care among challenging patients with HIV was evaluated. Twelve HIV care physicians participated, and their video recordings pre- and post-MI training were also obtained. One week post-training, 11 of the 12 participants were committed to using MI strategies during consult session. Of the 12 participants, 9 demonstrated appropriate utilization of MI techniques and change in HIV education provided during consultation ( Z = −2.375, P = .018). Motivational interviewing appears to be a viable strategy to enhance engagement and retention in challenging HIV-positive patients.